MANAJEMEN ASOSIASI SEPAKBOLA KABUPATEN (ASKAB) PSSI WONOSOBO - Afton Agata; Sugiarto (Sports Collaboration Journal, 2023)
Wonosobo is one of those cities where this hasn’t happened in recent years had good football achievements. Problems such as ineffective communication between organizations and parties that play an important role in determining good performance and there are no adequate training infrastructure.This study aims to find out how the management of the PSSI Wonosobo Regency Football Association is in implementing management functions in the PSSI Wonosobo Regency Football Association. This type of research is descriptive and qualitative. Data collection methods by observation, interviews, and documentation. Research subjects consisted of 6 respondents, namely 2 administrators, 2 coaches, and 2 Wonosobo football athletes. The data analysis techniques used is data reduction, data presentation, and drawing conclusions. The results of this study are (1) The implementation of the ASKAB PSSI Wonosobo program has been carried out well, (2) The training facilities and infrastructure are still very limited, (3) The management organization of the ASKAB PSSI Wonosobo program is in the process of improving the quality of performance. The conclusion from the results of this study is that the management of ASKAB PSSI Wonosobo which consuls of planning, organizing leadership and supervision has not gone well, there is still much that needs to be improved to make ASKAB PSSI Wonosobo even better. Abstrak Wonosobo adalah salah satu kota yang tidak memiliki kesuksesan sepakbola yang bagus dalam beberapa tahun terkahir. Masalah seperti komunikasi yang tidak efektif antara organisasi dan pihak yang berperan penting dalam menentukan kinerja yang baik dan kurangnya infrastruktur pelatihan yang memadai. Penelitian ini bertujuan untuk mengetahui bagaimana manajemen pengelolaan Asosiasi Sepakbola Kabupaten PSSI Wonosobo dalam menerapkan fungsi-fungsi manajemen di Asosiasi Sepakbola Kabupaten PSSI Wonosobo. Jenis penelitian ini adalah deskriptif kualitatif. Metode pengumpulan data melalui observasi, wawancara, dan dokumentasi. Subjek penelitian terdiri dari 6 responden yaitu 2 pengurus, 2 pelatih, dan 2 atlet sepakbola Wonosobo. Teknik analisis data yang digunakan adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini yaitu (1) Pelaksanaan program ASKAB PSSI Wonosobo sudah dilaksanakan dengan baik, (2) Sarana dan prasarana latihan yang masih sangat terbatas, (3) Penyelenggaraan program ASKAB PSSI Wonosobo saat ini sedang meningkatkan kualitas kinerjanya. Kesimpulan tentang hasil penelitian ini adalah manajemen ASKAB PSSI Wonosobo yang terdiri dari perencanaan, pengorganisasian kepemimpinan serta pengawasan belum berjalan dengan baik, masih banyak yang perlu ditingkatkan untuk menjadikan ASKAB PSSI Wonosobo lebih baik lagi.